Ivory Coast or the Strange Fate of the Foreigner - (:unkn) unknown (My University, 2003)
Coexistence among natives, outsiders and immigrants is part of ordinary daily life in urban or rural environments, but when it enters the political sphere and the mass media, it can become a social drama. While immigration is not a new issue In Ivory Coast, its utilization for political purposes is of recent date. While always present in public debate, immigration was never the basis of a real government policy nor did it lead to restructuring the national community.After more than three centuries of a very liberal attitude toward immigration, where immigrants were given the « right » to hold land and access to public employment, and allowed to participate in various elections, the Ivorian government has made marked changes in its regulations and has reformed the system so as to favour « real » Ivorians ; i.e., those of « native stock ». In this particularly tense climate where the Other is stigmatized, West African « brothers » are discovering their foreignness. Having become foreigners, and even enemies of Ivory Coast, they are led to contest, accept or reappropriate their new status. Naturalization, assimilation to the majority, retreating inward upon themselves, reconfiguring their relations with neighbours and work colleagues, valuing their uniqueness : all these figure among the responses to exclusion by Africans living in Ivory Coast.
Keywords: African Research